A Rare Coincidence of Two Coronary Anomalies in an Adult - Cesar Cruz; Dalton Mclean; Matthew Janik; Paolo Raggi; A. Maziar Zafari (Cardiology Research and Practice)
Anomalous right-sided left main coronary arteries and dual type IV left anterior descending arteries are rare coronary anomalies. In this case report, we present a 59 year old man with atypical chest pain and a combination of the above coronary anomalies as identified by selective coronary angiography and computed tomography angiography. To the best of our knowledge, the coincidence of these coronary anomalies has not been previously described.